Misa Leva: Bentuk Inkulturasi Iman Katolik dalam Budaya Masyarakat Lamalera - Lelangwayan, Petriana Dae; Intansakti Pius X; Tarihoran, Emmeria (Anugerah : Jurnal Pendidikan Kristiani dan Kateketik Katolik, 2025)
This article discusses the leva mass in Lamalera as one of the examples of the inculturation of the Catholic faith in local culture on the island of Lembata, East Nusa Tenggara. Inculturation is understood as a process of encounter between faith and culture, so that the proclamation of the gospel can be deeply lived in the context of the life of the local people. Through the leva mass, cultural elements such as sea symbols, boats (tena), traditional dances, traditional clothing, and regional songs are harmoniously integrated into the liturgy of the Catholic Church. For the Lamalera community, the sea is not only a source of livelihood, but a symbol of God's presence and power that blesses and protects human life. The celebration of the Mass emphasizes that God is present not only in the church building, but also in every aspect of human life, including work. The Leva Mass can also strengthen the spirit of brotherhood, solidarity, and the responsibility of the people towards His created nature. The people learn to be grateful for marine products, respect the environment, and work with the spirit of love and sacrifice. Thus, the leva mass is not just a religious ritual, but also a faith and cultural education that helps the people in understanding their call to live in harmony with nature and the will of God. Through the Mass of Leva, the Church in Lamalera portrays the living face of faith, the source of the gospel but rooted in the local culture.